Raman analysis of chemisorbed tribofilm for metal‐on‐polyethylene hip joint prostheses. Issue 1 (25th May 2021) - Rufaqua, Risha; Vrbka, Martin; Hemzal, Dušan; Choudhury, Dipankar; Rebenda, David; Křupka, Ivan; Hartl, Martin
Abstract: The biochemical reaction during the formation of lubricant film the in case of a cobalt‐chromium ball on an ultrahigh‐molecular weight polyethylene cup was studied. Three types of model synovial fluids and hyaluronic acid (HA) at physiologic concentrations were used in the experiment. The coefficient of friction was measured using a pendulum hip simulator, and Raman spectroscopy was used to perceive chemical reactions between the synovial fluid and implant material. Raman spectra evidenced that the three model fluids and HA chemisorbed onto the cobalt‐chromium surface. An α ‐helix structure of the model fluid components was detected on the surface of the prosthesis.